Dementia & Alzheimer's caregiving [ through the looking glass = Cuidados para la demencia y el Alzheimer : a traves del espejo = Demencia e alzheimer : cuidados especiais (Coastal Training Technologies, 2005)
(Producer's website) There are five million victims in the U.S. alone. This compelling program can help caregivers learn patience and exercise creative problem-solving techniques when dealing with patients.